Unlock the hidden powers of the iPhone & iPad. - Aguilera, Ray.; Berenstain, Adam.; Bohon, Cory.; Bookwalter, J.R.; Curthoys, Paul.; Ochs, Susie; Vargus, Nic.
Apple's phones and tablets can do loads of cool things right out of the box, but they really take off once you discover these expert-level tricks and techniques.
Keywords: iPhone (Smartphone); iPad (Computer); iOS (Electronic resource); Streaming technology (Telecommunications); Syncing; Photo management; iDevices